Benthic and fish community composition on mesophotic reefs in Grand Cayman - Le Gall, Lucas; Johnson, Jack V.; Chequer, Alex; Doherty, Matthew Louis; Goodbody-Gringley, Gretchen (PeerJ, 2024)
Mesophotic Coral Ecosystems (MCEs) represent unique ecological habitats that range from 30 to 150 m deep, harbouring phylogenetically distinct species and offering refuge for many taxa during times of environmental stress. Yet owing to inaccessibility of ecosystems at these depths, most MCEs remain unexplored, with quantifications of ecological communities in these habitats lacking across many regions. Here, using open- and closed-circuit technical diving, we quantified benthic and fish community composition at four mesophotic reef sites (45 m depth) in Grand Cayman. We show significant differences in benthic community composition over a small spatial scale driven by disparate coverage of sponges, crustose coralline algae, and sand/rubble, yet consistent patterns of macroalgal dominance representing >50% coverage at each site and low hard coral cover at an average of 2.4%. Reef fish species richness, biomass, and density was consistent across sites, however the relative contribution of individual species to community composition differed significantly. Macrocarnivores were found to be the dominant contributors to biomass, with invertivores the most speciose, and omnivores and planktivores at the highest densities, consistent with previous descriptions of mesophotic fish assemblages in other regions. Similarly, the low hard coral cover and high macroalgae and sponge cover of the benthic communities also appear ecologically similar to several described mesophotic reefs yet is not uniform across the Caribbean. The ecological organisation of Grand Cayman’s MCEs may result from a variety of factors such as isolation from other major land masses, geology, local geography, and anthropogenic activity at both the local and global scale and highlight the importance of continued exploration and documentation of MCE communities.
Keywords: Mesophotic reef; Benthic; Carribean; Fish community; Cayman Islands; Mesophotic; Coral reef; Assemblages; Macroalgae; Benthic cover